Electrochemical Hydrogen Compression: Efficient Pressurization Concept Derived from an Energetic Evaluation. Issue 12 (30th August 2017) - Suermann, Michel; Kiupel, Thomas; Schmidt, Thomas J.; Büchi, Felix N.
Abstract : Electrochemical hydrogen compression is a potentially high efficient, low-maintenance and silent technology to produce high pressure hydrogen. A new pressure concept with increased compression efficiency, termed intermediate differential pressure polymer electrolyte water electrolysis is proposed. With slightly pressurized oxygen and a much higher hydrogen pressure, this pressure concept profits from the advantages of the lower gas crossover of differential (only hydrogen compressed) pressure water electrolysis and the improved oxygen evolution reaction kinetics with increasing pressure of balanced pressure operation. Data for gas pressures up to 100 MPa is modeled, based on experimental results up to 5 MPa, of the three pressure concepts and validated with literature data up to 70 MPa. While differential pressure electrolyzer operation, following ideal isothermal compression, can be more efficient than today's best mechanical compressors up to 40 MPa, the intermediate pressure concept shows higher compression efficiency up to 90 MPa.